Geographic proximity, trade and international conflict/cooperation - John Robst; Solomon W. Polachek; Yuan-Ching Chang (Institute for the Study of Labor (IZA), 2006)
This paper examines the interactive effect of distance and trade on international conflict and cooperation. The effect of geographic distance depends on trade, while the effect of trade varies with geographic distance. Trade reduces conflict to a greater extent when dyads are geographically close, but has a greater effect on cooperation when countries are more distant. Geographic proximity increases conflict and cooperation more among non-trading dyads.
Keywords: A12; A13; F1; O57; 330; conflict; trade; distance; geographic proximity; cooperation; international relations; international interactions